Handbook of enterprise systems architecture in practice - Saha, Pallab, 1970- (Hershey, PA : Information Science Reference, 2007)
"This book is a valuable addition to the reading list of executives, managers, and staff in business, government, and other sectors who seek to keep their enterprises agile and efficient as they manage change, implement new business processes and supporting technologies, and pursue important strategic goals"--Provided by publisher.
Ηλεκτρονικό βιβλίο
Keywords: Management -- Data processing; Business enterprises -- Communication systems -- Management; Computer architecture; Management information systems; Electronic books